The use of crushed rubber in asphalt mixtures of road pavements - Holubka, Mariya; Salaiová, Brigita (Видавництво Львівської політехніки, 2013)
The presented article gives a brief overview on the possible use of crushed rubber from waste tires in asphalt mixtures. Advantages, disadvantages and difficulties of its use in road construction are also discussed. The results of sieve analysis and thermal analysis obtained on the samples prepared from waste rubber are discussed. The use of recycled tire rubber in road construction can contribute significantly to the reduction of environmental load. Коротко описано можливості застосування подрібненої гуми зі зношених автошин в сфальтобетонних сумішах. Обговорено переваги, недоліки і труднощі її використання в дорожньому будівництві, результати гранулометричного складу і термічного аналізу зразків гуми, виготовленої з автошин, що були у вжитку. Використання гуми з автошин у дорожньому будівництві може зробити значний внесок у зниження навантаження на навко л ишнє середовище.
Keywords: ground tire rubber; hot mix asphalt; sieve analysis; thermal analysis; гранулована гума з автошин; гарячі асфальтні суміші; гранулометрія; термічний аналіз